THE RELATIONSHIP BETWEEN DIET AND PHYSICAL ACTIVITY WITH BODY MASS INDEX (BMI) IN ADOLESCENTS AT SMAN 9 JAKARTA - Karyadi, Karyadi; Tisya Yulia Sari,; Edi Gunawan,; Jamaludin, Jamaludin (Journal of Innovation Research and Knowledge, 2025)
Background: Physical activity and diet are one of the factors of nutritional problems that will affect the growth and development of adolescents. In Indonesia, the prevalence of overnutrition and undernutrition in adolescents aged 16-18 years has increased. The role of nurses as educators and implementers of nursing care can improve health status in adolescents. Objective: This study is to determine the relationship between diet and physical activity with body mass index of adolescents at SMAN 9 Jakarta. Methods: This type of research is quantitative with correlation analytic design using cross sectional approach. Results: The results of the study from 102 respondents showed that the majority of body mass index was categorized as healthy weight 60.8%, moderate physical activity 59.8%, and poor diet 50.0%. The results of the Spearman's rho correlation test of dietary variables obtained p value = 0.000 so that p < α then, there is a relationship between diet and body mass index at SMAN 9 Jakarta with a strong closeness value of 0.507 and positive direction. The physical activity variable obtained p value = 0.511 so that p> α then, there is no relationship between physical activity and body mass index at SMAN 9 Jakarta with a very weak 0.066 and positive direction. Diet and physical activity are important to pay attention to in order to achieve a normal body mass index, especially for adolescents.